(untitled) (Bangladesh Journal of Child Health, 2017)
Background: Systemic JIA (sJIA) is the most severe sub type of JIA with limited treatment option and responsible for most of the disability and morbidity in JIA. Objective: To assess the efficacy of Tocilizumab (TCZ) in refractory sJIA patients according to disease activity score in 28 joint criteria. Methodology: This interventional study was carried in the department of Paediatrics, Bangabandhu Sheikh Mujib Medical University (BSMMU). A total number of 22 sJIA patients who were refractory to traditional DMARDs were offered TCZ. Among them 15 patients agreed to take TCZ (cases) and 7 patients did not (controls). All the cases and controls were assessed according to DAS 28 criteria at enrollment, 12 weeks and 24 weeks of TCZ therapy. DAS 28 scores during assessment were compared. Results: After TCZ therapy systemic features subsided and laboratory features improved in 100% cases. Among cases 93.3% and 92.3% had moderate response at 12 and 24 weeks respectively according to DAS 28 criteria. Among controls 71.5% and 85.7% had moderate response at 12 and 24 weeks respectively (p0.001). Among cases 40% and 60% patients achieved remission at 12 and 24 weeks, where as among controls none achieved remission. Dose of steroid was significantly reduced among cases but was increased significantly among controls. Few side effects like pharyngitis, Varicella, septicemia, anaphylactoid reaction and raised ALT were observed. Conclusion: Tocilizumab therapy was effective according to DAS 28 criteria refractory sJIA. Bangladesh J Child Health 2015; VOL 39 (3) :129-134